BIOBRIKET KARBONISASI DARI CANGKANG METE DAN SEKAM PADI UNTUK ENERGI BERKELANJUTAN - Lukas Kano Mangalla; Abd. Kadir; Kadir Kadir (Dinamika : Jurnal Ilmiah Teknik Mesin, 2019)
Indonesia - an agricultural country- has a large potential of biomass waste such as cashew nut shells and rice husks. Utilization of these materials can be an important source of alternative energy to support sustainable energy development. Several methods have been developed to optimize the utilization of this biomass throughout compacting processes at high pressures and temperatures as well as a material admixture. This study aims to investigate the energy potential of bio-briquettes from cashew nut shell charcoal and rice husks made of various pressures and materials admixture. The composition of briquette material consists of cashew charcoal (M) and rice husk (S) with a composition of 30/70 %, 50/50 % and 70/30% (mass base) with a constant adhesive of 15%. Each composition admixture was taken 5 grams to be compacting as briquettes. Bio-briquettes are made in cylindrical shapes with compacting pressures ranging from 50, 100 and 150 kgf /cm2. Combustion testing is carried out in solid fuel testing furnaces equipped with K-Type thermocouple and digital scales to measure the combustion temperature and combustion rate of the briquette mass when burned. The results showed that cashew charcoal shells and rice husks are very potential to be used as solid fuels which have a coal equivalent heating value. The larger the admixture of cashew nut charcoal in bio-briquettes the better the thermal properties derived, especially of combustion rate and temperature generated during combustion.